1990
DOI: 10.1210/endo-127-2-621
|View full text |Cite
|
Sign up to set email alerts
|

Calcitonin Inhibits Basal and Thyrotropin-Releasing Hormone-Induced Release of Prolactin from Anterior Pituitary Cells: Evidence for a Selective Action Exerted Proximal To Secretagogue-Induced Increases in Cytosolic Ca2+*

Abstract: Salmon calcitonin (sCT)-like peptide is present in the central nervous system and pituitary gland of the rat, and this peptide inhibits basal and TRH-stimulated PRL release from cultured rat anterior pituitary (AP) cells. The present studies were designed to examine further the inhibitory actions of sCT on basal and TRH-stimulated PRL release and investigated 1) the temporal dynamics of the responses, 2) the effects of sCT on PRL release induced by other secretogogues, and particularly those acting via elevati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Calcitonin-like immunoreactive material has been detected, is synthesised and released by rat and chicken pituitary cells ( 240 – 242 ), is present in rat gonadotrophs ( 189 ) and in an ÎąGSU expressing cell line ( 243 ), and the pituitary also expresses the calcitonin receptor ( 244 ). Treatment of pituitary cell cultures with calcitonin inhibits basal and TRH-stimulated PRL release ( 245 , 246 ), lactotroph mitosis and PRL mRNA expression ( 247 ), but not TRH-induced TSH release or GnRH-induced LH release ( 245 ). Conversely, treatment of the cultures with an anticalcitonin antibody enhances PRL mRNA expression and PRL release ( 241 ), as well as lactotroph mitosis ( 247 ), suggesting that endogenous calcitonin is tonically active in a paracrine manner.…”
Section: Gonadotrophs Signal To Lactotrophs Somatotrophs and Corticomentioning
confidence: 99%
“…Calcitonin-like immunoreactive material has been detected, is synthesised and released by rat and chicken pituitary cells ( 240 – 242 ), is present in rat gonadotrophs ( 189 ) and in an ÎąGSU expressing cell line ( 243 ), and the pituitary also expresses the calcitonin receptor ( 244 ). Treatment of pituitary cell cultures with calcitonin inhibits basal and TRH-stimulated PRL release ( 245 , 246 ), lactotroph mitosis and PRL mRNA expression ( 247 ), but not TRH-induced TSH release or GnRH-induced LH release ( 245 ). Conversely, treatment of the cultures with an anticalcitonin antibody enhances PRL mRNA expression and PRL release ( 241 ), as well as lactotroph mitosis ( 247 ), suggesting that endogenous calcitonin is tonically active in a paracrine manner.…”
Section: Gonadotrophs Signal To Lactotrophs Somatotrophs and Corticomentioning
confidence: 99%
“…Previous findings from this laboratory have shown that exogenously added SCT significantly attenuates prolactin (PRL) release from perifused rat AP cells without altering the secretion of growth hormone (GH), folliclestimulating hormone, luteinizing hormone (LH) or thyroid stimulating hormone (Shah et al 1988(Shah et al , 1990. SCT is also a potent inhibitor of PRL gene transcription and lactotrope cell proliferation in rats (Zhang et al 1995, Shah et al 1999.…”
Section: Introductionmentioning
confidence: 99%
“…While F has been found to inhibit PRL, the molecular mechanisms behind this of inhibition remain unclear. However, it is important to note that CT is a PRL-inhibiting hormone [151,161,162,163,164]. As previously discussed, F has been found to be a potent inducer of CT expression in humans [152,153,154,155,156,157].…”
Section: Molecular Mechanisms Of Fluoride Inhibition Of Iodine Hommentioning
confidence: 99%